Visfatin is a multifaceted molecule that exerts regulation effects on inflammation and apoptosis in RAW264.7 cells and mice immune organs - Zhang, Zhewei; Xiao, Ke; Wang, Sheng; Ansari, Abdur Rahman; Niu, Xiaoyu; Yang, Wenjie; Lu, Mengqi; Yang, Zhi; Rehman, Zia ur; Zou, Weihua; Bei, Weicheng; Song, Hui (Frontiers in Immunology, 2022)
Visfatin, a multifunctional adipocytokine, is particularly important in the regulation of apoptosis and inflammation through an unidentified mechanism. Clarifying the control mechanisms of visfatin on inflammation and apoptosis in RAW264.7 cells and mice immunological organs was the goal of the current investigation. In order to create a pathophysiological model, the RAW264.7 cells were stimulated with 200 ng/mL visfatin and 20 μg/mL lipopolysaccharide (LPS), either separately or combined. The effects of exogenous visfatin on inflammation and apoptosis in RAW264.7 cells were investigated by flow cytometry assay, RNA-Seq analysis and fluorescence quantitative PCR. According to the findings, exogenous visfatin exhibits dual effects on inflammation by modulating the expression of IL-1α, Tnfrsf1b, and Lif as well as taking part in a number of signaling pathways, including the MAPK and Rap1 signaling pathways. By controlling the expression levels of Bcl2l1, Bcl2a1a, and Fas and primarily participating in the PI3K/AKT signaling pathway and Hippo signaling pathway, exogenous visfatin can inhibit apoptosis in RAW264.7 cells. In order to further confirm the effects of endogenous visfatin on inflammation and apoptosis in mice immune organs, the expression of endogenous visfatin in mice was inhibited using the visfatin inhibitor FK866. Subsequently, mice spleen and thymus were collected. It is interesting to note that in LPS-treated mice, suppression of endogenous visfatin might worsen the immune system's inflammatory response and even result in rapid mortality. Additionally, endogenous visfatin promotes the apoptosis in mice immune organs by regulating the expression levels of Bcl2l1, Fas, Caspase 3, Bcl2a1a, and Bax. Together, these results imply that visfatin is a multifaceted molecule that regulates inflammation and apoptosis in RAW264.7 cells and mice immunological organs by taking part in a variety of biological processes and regulating the amounts of associated cytokines expression. Our findings offer additional understandings of how visfatin affects apoptosis and inflammation.